Couples coping with advanced prostate cancer: an explorative study on treatment decision making, mental deterioration, partnership, and psychological burden - Ihrig, Andreas; Hanslmeier, Tobias; Grüllich, Carsten; Zschäbitz, Stefanie; Huber, Johannes; Greinacher, Anja; Sauer, Christina; Friederich, Hans-Christoph; Maatouk, Imad (Urologic oncology, 2022)
Objectives - The aim of this study was to evaluate the role of spouses and the relevance of quality of life (QoL) and life expectancy (LE) in the treatment decision-making process of patients with advanced prostate cancer (CaP). We also addressed the role of possible mental deterioration, partnership quality, QoL, distress, anxiety, and depression in patients and their spouses. - Methods and Material - This was a cross-sectional non-interventional explorative study. We administered questionnaires to 96 patients with advanced CaPand their spouses. Both patients and their spouses were asked about the influence of the spouses on treatment decision making, if they prefer quality of life or life expectancy as main goal of treatment and the perceived deterioration of the patients’ mental abilities. Additional questionnaires were used to assess medical history, partnership, global quality of life, distress, depression, and anxiety. We performed statistical tests to compare patients with spouses and correlations to detect associations between variables. - Results - The spouses (65 ± 9 years) were significantly younger than the patients (69 ± 9 years). Ninety-five percent of the patients and 91% of the spouses reported that the spouses were involved in making treatment decisions. There was a high similarity within couples with regard to their preference for QoL or LE during treatment. Between couples, this preference differed markedly. Emotional control and motivation were the areas most commonly reported to have deteriorated among patients’ mental abilities. The quality of the partnership was rated as being higher than average by both partners. Among the spouses, the quality of partnership correlated significantly with the preference for LE with regard to treatment decision making. Patients and spouses reported high psychological burdens in all areas, with higher levels of distress and anxiety in spouses (P< 0.01). Reduced quality of life and greater distress, depression, and anxiety were significantly correlated with the amount of deterioration of the patients’ mental abilities. - Conclusions - Spouses of patients with advanced CaP seem to respond to different aspects of the disease by adjusting both their involvement in treatment decision making and their preferred goal of treatment. Due to mental deterioration in the patients and pronounced anxiety in their spouses, we suggest that it is important for the attending physician to provide detailed information and support to both partners. Overall, the high-stress situation seems to affect both partners to similar degrees.